Los clérigos de La familia de León Roch, de Pérez Galdós. - Krauel, Ricardo. (University of Ottawa (Canada), 1993)
This Master's thesis contains a study of the clerical figures in the novel La familia de Leon Roch, by Benito Perez Galdos. Its main objective is to determine to what extent the author has utilized these characters as ideological vehicles for the expression of a particular attitude with regards to the "religious question," which aroused much concern and debate in the Spanish society (and prose fiction) of the Restoration. To this end, the two priest figures (Luis Gonzaga Sudre and Father Paoletti) who play roles of certain import in the novel have been analysed, considering the manner in which they have been characterized, their participation in the plot events and dialogues, and their relationships with, and influence on, other characters; in other words, all textual references which might in any way help to clarify the ideological function performed in the novel by these two ecclesiastical figures have been carefully considered. (Abstract shortened by UMI.)
Keywords: Literature, Modern.